Life cycle comparative assessment of pet bottle waste management options: A case study for the city of Bauru, Brazil - Martin, Eduardo J.P. [UNESP]; Oliveira, Deborah S.B.L.; Oliveira, Luiza S.B.L.; Bezerra, Barbara S. [UNESP] (Elsevier, 2021)
This study analyzed the environmental impacts of nine scenarios for Polyethylene Terephthalate (PET) bottle waste disposal, in the city of Bauru, Brazil. Nine scenarios were considered in this study: (1) current (base) scenario (96.4% of PET waste is sent to landfill, 3.6% is sent to sorting cooperatives); (2) 50% to sorting cooperatives, 50% to landfill; (3) 50% to sorting cooperatives, 50% to incineration; (4) 50% to landfill, 50% to incineration; (5) 100% to sorting cooperatives (keeping the current collection distribution); (6) 100% to landfill; (7) 100% to incineration; (8) and (9) 100% sent to sorting cooperatives, with changes in the collection scheme. Life cycle assessment was implemented to compute the impacts for each scenario and compare their environmental performances. The results have shown that recycling is a better option than incineration across all impact categories analyzed. Landfilling had lower net impacts than incineration in all categories, except for ozone depletion and freshwater eutrophication. All recycling scenarios proposed outperformed the current scenario in all impact categories. Even though recycling presents itself as an environmentally-promising alternative, much work still needs to be done for its successful implementation, such as promoting source-separation at home and improving the management strategies of recycling cooperatives, including additional funding and training to support an increased sorting capacity.
Keywords: Incineration; Landfilling; Life cycle assessment; Polyethylene Terephthalate (PET) waste; Recycling